2017
DOI: 10.1107/s1600577517010955
|View full text |Cite
|
Sign up to set email alerts
|

Insight into 3D micro-CT data: exploring segmentation algorithms through performance metrics

Abstract: Three-dimensional (3D) micro-tomography (µ-CT) has proven to be an important imaging modality in industry and scientific domains. Understanding the properties of material structure and behavior has produced many scientific advances. An important component of the 3D µ-CT pipeline is image partitioning (or image segmentation), a step that is used to separate various phases or components in an image. Image partitioning schemes require specific rules for different scientific fields, but a common strategy consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Our motivator to pursue this work was an image processing problem that required maximal cliques and also aimed to support multiple architectures. In fact, very recent algorithms for the analysis of experimental image data take advantage of graphical models with maximal clique analysis and high performance computing techniques as in [37,38]. That said, we have found that, for certain conditions, our approach is competitive with leading maximal clique implementations.…”
Section: Introductionmentioning
confidence: 76%
“…Our motivator to pursue this work was an image processing problem that required maximal cliques and also aimed to support multiple architectures. In fact, very recent algorithms for the analysis of experimental image data take advantage of graphical models with maximal clique analysis and high performance computing techniques as in [37,38]. That said, we have found that, for certain conditions, our approach is competitive with leading maximal clique implementations.…”
Section: Introductionmentioning
confidence: 76%
“…The process of segmenting an image involves separating various phases or components from a picture using photometric information and/or relationships between pixels/regions representing a scene. This essential step in an image analysis pipeline has been given great attention recently when studying experimental data [29]. There are several different types of image segmentation algorithms, which can be divided into categories, such as: threshold-based, region-based, edge-based, clustering-based, graph-based, and learning-based techniques.…”
Section: Mrf-based Image Segmentationmentioning
confidence: 99%
“…The process of segmenting an image involves separating various phases or components from the picture using photometric information and/or relationships between pixels/regions representing a scene. This essential step in an image analysis pipeline has been given great attention recently when studying experimental data [38]. There are several different types of image segmentation algorithms, which can be divided into categories such as: threshold-based, region-based, edge-based, clustering-based, graph-based and learning-based techniques.…”
Section: Mrf-based Image Segmentationmentioning
confidence: 99%
“…For the purposes of this analysis, we corrupted the original stack by noise (salt-and-pepper) and additive Gaussian with σ = 100. Additionally, we also simulate ringing artifacts [38] into the sample to closer resemble real-world results. For the segmentation algorithm analysis, the corrupted data serves as the "original data" and the binary stack as the ground-truth.…”
Section: Datasetsmentioning
confidence: 99%